Pengaruh Vulva Hygiene Terhadap Pencegahan Risiko Infeksi Luka Ruptur Perineum - busroh, khafiatun; Yuni Purwati (2025)
Vulva hygiene is cleaning the vulva and surrounding area in postpartum maternal patients. Perineal rupture is a laceration that occurs in the genital area (perineum) directly or using a tool. One of the steps that mothers can take is with vulvar hygiene. The purpose of her research was to be able to manage postpartum nursing care for Mrs.